Geophysical modeling of collapse‐prone zones at Rumble III seamount, southern Pacific Ocean, New Zealand. (18th October 2013) - Tontini, F. Caratori; de, C. E. J.; Kinsey, J. C.; Soule, A.; Yoerger, D.; Cocchi, L.
<x xml:space="preserve">Abstract</x> [1] Catastrophic collapses of submarine volcanoes have the potential to generate major tsunami, threatening many coastal populations. Recognizing the difficulties surrounding anticipations of these events, quantitative assessment of collapse‐prone regions based on detailed morphological, geological, and geophysical mapping can still provide important information about the hazards associated with these collapses. Rumble III is one of the shallowest, and largest, submarine volcanoes found along the Kermadec arc, and is both volcanically and hydrothermally active. Previous surveys have delineated major collapse features at Rumble III; based on time‐lapse bathymetry, dramatic changes in the volcano morphology have been shown to have occurred over the interval 2007–2009. Furthermore, this volcano is located just ∼300 km from the east coast of the North Island of New Zealand. Here, we present a geophysical model for Rumble III that provides the locations and sizes of potential weak regions of this volcano. Shipborne and near‐seafloor geological and geophysical data collected by the AUV Sentry are used to determine the subsurface distribution of weak and unstable volcanic rocks. The resulting model provides evidence for potentially unstable areas located in the Southeastern flank of this volcano which should be included in future hazard predictions.